Droplet Microfluidics for Advanced Single‐Cell Analysis - Liu, Chang; Xu, Xiaoyu (Smart medicine, 2025)
ABSTRACT Droplet microfluidics has emerged as a breakthrough technology that is changing our comprehension of single‐cell and their associated research. By separating individual cells within tiny droplets, ranging from nanoliters to picoliters using microfluidic devices, this innovative approach has revolutionized investigations at the single‐cell level. Each of these droplets serves as a distinct experimental reaction vessel, enabling thorough exploration of cellular phenotypic variations, interactions between cells or cell‐microorganisms as well as genomic insights. This review paper presents a comprehensive overview of the current state‐of‐the‐art in droplet microfluidics, which has made single‐cell analysis a practical approach for biological research. The review delves into the technological advancements in single‐cell encapsulation techniques within droplet microfluidics, elucidating their applications in high‐throughput single‐cell screening, intercellular and cell‐microorganism interactions, and genomic analysis. Furthermore, it discusses the advantages and constraints of droplet microfluidic technology, shedding light on critical factors such as throughput and versatile integration. Lastly, the paper outlines the potential avenues for future research in this rapidly evolving field. This paper reviews the transformative impact of droplet microfluidics on single‐cell research. It highlights current advancements in encapsulation techniques, applications in high‐throughput screening, and the study of intercellular and cell‐microorganism interactions. The discussion includes the advantages, limitations, and future research directions of this innovative technology in biological investigations.